Repeated Exposure of Native African Adansonia Digitata (Baobab) and Moringa Oleifera (Moringa) Modifies Caco-2 Cell Differentiation but Not Carotenoid Absorption (P10-025-19). (13th June 2019) - Debelo, Hawi; Corbin, Sydney; Chegeni, Mohammad; Ferrara, Francesca; Valacchi, Giuseppe; Ferruzzi, Mario
Abstract: Objectives: The inclusion of mineral rich African plants such as moringa ( Moringa oleifera ; MOR) and baobab ( Adansonia Digitata ; BB) into composite cereal porridges is a potentially sustainable strategy to providing key shortfall micronutrients including iron and zinc to at risk populations. However, only limited information is available on long term health effects of these materials including their potential to modify gut barrier function or their impact on absorption of other nutrients such as provitamin A carotenoids(pVAC). The present study investigated the impact of repeated exposure of MOR and BB to the human intestinal cell model (Caco-2) to assess changes in intestinal cell differentiation and subsequent pVAC uptake from model foods. Methods: To study gut impacts from BB and MOR exposure at usage rate of 15% of a cereal porridge, Caco-2 cells were cultured and differentiated on 6 well plates for 10–14d with complete media containing digested BB (15%), moringa (15%) or saline (control) in a 1:8–12 ratio (v/v). Caco-2 cell differentiation was followed by 1 H NMR and pVAC transporter by QRT-PCR and Western blotting. Cellular uptake of pVACs in differentiated monolayers was assessed for 4 h from a final acute dose of digested carrots (3590 mg/100 g total proVAC) estimated to deliver ∼30% of the RDA for VA. Results: Alterations in select Caco-2 cell differentiation biomarkers were observed by NMR from repeated exposure to all treatments. Specifically, glycerophosphocholine and taurine were observed to significantly increase with repeated exposure to all treatments. Significant reduction ( P  < 0.05) in carotenoid uptake was observed following repeated exposure across all treatment groups. No significant differences between control and baobab or moringa treatment. Despite the reduction in carotenoid uptake, mRNA and protein levels of carotenoid transporters (CD-36, SR-B1 and FABP1) were not significantly altered by chronic exposure to BB or MOR suggesting reduced transport is a product of prolonged accumulation of background digesta matrix. Conclusions: Overall, at the levels explored in this study, mineral-rich BB or MOR do not appear to negatively impact differentiation of Caco-2 cells or their ability to accumulate pVAC carotenoids over prolonged exposure. Funding Sources: USAID Food Processing & Post Harvest Innovation Lab. Sorghum & Millet Innovation Lab.